Evaluating the interactions between aging, running, and APOEε4 on systemic and cerebral risk factors for dementia - Foley, Kate. (Tufts University. Tisch Library., 2022)
Thesis (Ph.D.)--Tufts University, 2021.; Submitted to the Dept. of Genetics.; Advisor: Gareth Howell.; Committee: Robert Burgess, Jennifer Trowbridge, and Gordon Huggins.; Keywords: Genetics, and Neurosciences.